2020
DOI: 10.3991/ijim.v14i07.11900
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Applications to Improve English Writing Skills Viewed from Critical Thinking Ability for Pre-Service Teachers

Abstract: This study was aimed at investigating; (1) the pre-service teachers used the MobApps (WhatsApp, U-Dictionary, and Email) to participate in mobile-assisted language learning (MALL) viewed from the critical thinking ability in the teaching of writing skills and; (2) the effectiveness of the Mobile-assisted language learning (MALL) towards pre-service teachers’ writing skills in relation to critical thinking ability. This study was a mixed method using the concurrent embedded strategy. The researchers involve qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
50
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 45 publications
(45 reference statements)
7
50
0
1
Order By: Relevance
“…Mobile devices can improve interactive communication between teachers and students, leading to the improvement of students' motivation in learning (Kopf, Scheele, Winschel, & Effelsberg, 2005). In addition, another aspect to be considered in EFL context is students' motivation and self-efficacy to learn (Haerazi & Irawan, 2020).…”
Section: English Pronunciation App and Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Mobile devices can improve interactive communication between teachers and students, leading to the improvement of students' motivation in learning (Kopf, Scheele, Winschel, & Effelsberg, 2005). In addition, another aspect to be considered in EFL context is students' motivation and self-efficacy to learn (Haerazi & Irawan, 2020).…”
Section: English Pronunciation App and Motivationmentioning
confidence: 99%
“…Smartphones made positive effects on learning English (Klimova, 2018;Haerazi, Utama, & Hidayatullah, 2020). A research conducted by Wu (2015) proved that college students taught using app significantly outperformed the controlled one in vocabulary acquisition.…”
Section: Introductionmentioning
confidence: 99%
“…There are several studies which reported in a recent research paper, [11] stated that digital storytelling had a positive impact on the writing skills of the students. MALL had a positive impact on the improvement of the Indonesian pre-service teacher's writing skills from a critical thinking point of view as stated in [12]. The use of interactive mobile applications showed a significantly positive impact in improving the reading and writing skills of Spanish students at the primary level [13].…”
Section: Related Literaturementioning
confidence: 84%
“…The addition of the MoLearn application with the Android version is because Mobile technology is considered an effective way to improve student skills such as positive thinking, collaborative thinking, communication, and is considered a major part of innovation in many fields of e-learning research [28]. Besides, research from Haerazi et al [29] states that learning with Mobile Apps can improve critical thinking skills in teaching writing skills.…”
Section: Introductionmentioning
confidence: 99%